The Use of Virtual Measuring Devices in Teaching Modeling of Physical Processes - Bidaybekov, L.B.; Bidaybekov, E.I.; Sharmukhanbet, S.; Kamalova, G.B.; Oshanova, N.T. (Procedia, social and behavioral sciences, 2012)
Informatization of education makes to reconsider traditional training courses of computer science, methods, technologies and the means of informatization applied in teaching other subjects. In this article we consider the problem of the creation and use of virtual measuring devices in teaching modeling of physical processes. The difficult or costly experimental conditions, the new equipment, the risks connected with carrying out of tests, bulky procedure of mathematical calculations, frequently lack of material resources, considerably constrain process of physical researches. Emergence of virtual laboratory of stands and simulators became one of solutions of a problem. The resulting stage of modeling is computing experiment, so in teaching modeling it is necessary to use virtual laboratory work - connected animated images, which simulate the experimental installation. The special system of virtual switches, windows to set parameters of experiment and manipulation with the mouse allow students to change operatively conditions of experiment and to make calculations or to build charts. Pedagogical meaning of laboratory researches is that students do the analysis results of modeling and conclusions himself. Application of such laboratory complexes allows making experiments, to observe and manage them in real time using a personal computer, that provides improvement quality of teaching and learning of teaching materials by students. Virtual laboratory installations supplement real laboratory installations. This is explained by the modeling capabilities of real experiment, high reliability of their work and rather low cost. As at performance of laboratory works most part of time is spent on understanding how to work with the installation, by downloading a virtual installation, the student has the opportunity to prepare in advance, having mastered the laboratory equipment, examining its performance in different modes. Using technology of virtual devices, it is possible to fully reproduce the actual installation as a virtual model, keeping all its functionality. Virtual installations on the monitor screen have visual similarity to real installations. Convenient management of the program facilitates understanding of studied processes. Also it is possible to create virtual devices. For today the most powerful and reliable tool for the development of virtual devices is the environment of graphic programming LabView of company National Instruments. This article contains the steps in conducting of laboratory workshop, their sequence promotes increase of effectiveness of the work, increases relationship of steps and lowers their complexity.